Expression analysis of Cinnamyl Alcohol Dehydrogenase (CAD) involved in lignin biosynthesis of Erianthus arundinaceus - Kasirajan, Lakshmi; Valiyaparambath, Rabisha (Journal of Sugarcane Research, 2021)
Erianthus arundinaceus has a great potential in bioenergy production and green-house gas mitigation due to its biological characteristic of huge biomass yield and stress tolerance. Our earlier transcriptome studies on a set of sugarcane genotypes differing for lignin content, showed that Cinnamyl Alcohol Dehydrogenase (CAD), was differentially expressed and of plays a major role in genetic regulation of lignin production, stem development and defense. This study aims to characterize the CAD gene and its expression in BL 21 E. Coli strain. In this context, understanding the regulatory functions of CAD gene would be more useful for achieving reduced lignin content and to have a cost-effective biomass conversion in sugarcane. Using bioinformatic tools like ExPasy and Prosite, the sugarcane CAD was found to belong to the Class I with affinity towards coniferyl aldehyde, sinapyl aldehyde with a predicted molecular weight of 46kDa.